Education and HIV/AIDS : a sourcebook of HIV/AIDS prevention programs - Valerio, Alexandria, 1968-; Bundy, Donald A. P. (Africa Region human development series., 2004)
"The book will be of interest to those in the fields of public health, social policy, and economic development, and particularly to policymakers and educators responsible for designing and implementing HIV/AIDS education programs."--Jacket